Structural revision of two unusual rhamnofolane diterpenes, curcusones I and J, by means of DFT calculations of NMR shifts and coupling constants. Issue 6 (16th January 2018) - Sarotti, Ariel M.
Abstract : The structures of two unusual rhamnofolane diterpenes, curcusones I and J, have been revised using quantum calculations of NMR shifts. Abstract : The stereochemical revision of two recently reported rhamnofolane diterpenes, curcusones I and J, was enabled by quantum calculations of NMR shifts and coupling constants at DFT levels. DP4+ results and reexamination of the NMR data suggest that curcusones I and J should be revised asCS32 andCS28, respectively.